P‐Cresyl sulfate, a uremic toxin, causes vascular endothelial and smooth muscle cell damages by inducing oxidative stress. Issue 1 (7th November 2014) - Watanabe, Hiroshi; Miyamoto, Yohei; Enoki, Yuki; Ishima, Yu; Kadowaki, Daisuke; Kotani, Shunsuke; Nakajima, Makoto; Tanaka, Motoko; Matsushita, Kazutaka; Mori, Yoshitaka; Kakuta, Takatoshi; Fukagawa, Masafumi; et al.
Abstract The major cause of death in patients with chronic kidney disease (CKD) is cardiovascular disease. Here, p‐Cresyl sulfate (PCS), a uremic toxin, is considered to be a risk factor for cardiovascular disease in CKD. However, our understanding of the vascular toxicity induced by PCS and its mechanism is incomplete. The purpose of this study was to determine whether PCS enhances the production of reactive oxygen species (ROS) in vascular endothelial and smooth muscle cells, resulting in cytotoxicity. PCS exhibited pro‐oxidant properties in human umbilical vein endothelial cells (HUVEC) and aortic smooth muscle cells (HASMC) by enhancing NADPH oxidase expression. PCS also up‐regulates the mRNA levels and the protein secretion of monocyte chemotactic protein‐1 (MCP‐1) in HUVEC. In HASMC, PCS increased the mRNA levels of alkaline phosphatase (ALP), osteopontin (OPN), core‐binding factor alpha 1, and ALP activity. The knockdown of Nox4, a subunit of NADPH oxidase, suppressed the cell toxicity induced by PCS. The vascular damage induced by PCS was largely suppressed in the presence of probenecid, an inhibitor of organic anion transporters (OAT). In PCS‐overloaded 5/6‐nephrectomized rats, plasma MCP‐1 levels, OPN expression, and ALP activity of the aortic arch were increased, accompanied by the induction of Nox4 expression. Collectively, the vascular toxicity of PCS can be attributed to its intracellular accumulation via OAT, which results in an enhanced NADPH oxidase expression and increased ROS production. In conclusion, we found for the first time that PCS could play an important role in the development of cardiovascular disease by inducing vascular toxicity in the CKD condition.